Лесной дозор: [повесть-сказка] / Елена Хрусталёва - Хрусталёва Е.Н. (Прикольный детектив, 2010)
Экземпляры: ДБ (20111102) / Инвентарный номер: 43477 / Цена: 173.52 / Авт.знак: Х 95 / ББК: 84(2Рос=Рус)6